Localism Principle in the Formulation of Indonesian Regulations on Pornography - Zulkifli Rahmat (Komunikator, 2020)
The Law on Pornography is perceived as not reflecting the nationality, the archipelago values, and legal certainty. However, the officials who formulated this policy were deemed to have failed in establishing a clear definition of pornography, which later contributed to the high ambiguity and legal uncertainty of the bill, now an Act. The analysis carried out in this writing focuses on the use of the principle of localism in the preparation of regulations of Law Number 44 of 2008 on Pornography. The approach method used in this qualitative research was the analytical description approach. The formulation of regulations in Indonesia must reflect the principles of protection, humanity, nationality, kinship, recollection as part of the archipelago, unity in diversity, justice, equality before law and government, order and legal certainty and/or balance, harmony, and conformity. The localism principle requires clear and mutually agreed interpretation, it would be useful in policymaking and policy analysis. Surely, the aim is to formulate a policy that contains clear and consistent evaluative and substantive standards. This research showed that the law on pornography, were born as a result of the localism principle not being used as a guideline at the beginning of its formulation.